Zgradba in delovanje vidne poti pri človeku - Brecelj, Jelka (Medicinski razgledi, 1999)
The authors present the fundamentals and some recent data on the human visal pathway obtained by the new imaging techniques of the cerebral cortex and non-invasive electrophysiological and other methods. Perception of colours andmotion is explained in the light of the new findings of parallel parvocellular (P) and magnocellular (M) pathways. Discrimination of colours isrendered possible by the following important structures of the P pathway: P ganglion cells in the retina - parvocellular layers in the thalamic lateral geniculate nucleus (LGN) - "blob" regions in the primary visual cortex V1 - V4visual area. Important structures of the M pathway providing for the discrimination of motion include: M ganglion cells in the retina-magnocelllular layers in the LGN-primary visual cortex V1 - V5 visual area. Location of other cortical areas involved in vision is presented; the visual pathway responsible for what is seen ends in the temporal cortex, and the pathway concerned with motion (where the objects are) ends in the parietalcortex. Clinical data for cerebral achromatopsia (complete colour blindness), akinetopsia (inability to discern movement of objects), prosopagnosia (inability to recognise familiar faces), also speak for the existence of several functionally specialised visual cortical areas. For the conscious perception of light and movement simultaneous activity of several visual areas seems to be necessary.
Keywords: oči; Visual cortex; Visual pathways; vid; Visual perception; fiziologija; mrežnica; Retina; Vision; motnje; Optic disk; Optic nerve; Optic lobe; Macula lutea; Fovea centralis; Color perception; Geniculate bodies; Vision, binocular; Visual fields; Vision disorders